Beneficial contribution of regional assistance in the effectiveness of dispute settlement within the World Trade Organization: comparison of trade dispute settlement between Russia v. EU and Russia v. Japan - Bindule, Katrīna (Riga Graduate School of Law, 2020)
The main objective of this research is to compare the effectiveness of the World Trade Organization Dispute Settlement Body in context of two specific cases: DS462: Russian Federation - Recycling Fee on Motor Vehicles and DS463: Russian Federation - Recycling Fee on Motor Vehicles. These cases share common legal provisions of Russia, which are challenged by two different counter parties - the EU and Japan. However, despite highly similar context of the cases, their course of resolution differentiate. In this regard, main goal of this comparative analysis is to find a shortage in the WTO DSB, which could possibly be solved by the assistance of other regional organizations
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Dispute settlement; World Trade Organization